Principles of successful implementation of lecture recordings in higher education. Issue 1 (18th April 2017) - Ollermann, Frank; Rolf, Rüdiger; Greweling, Christian; Klaßen, André
Abstract : Purpose: This paper aims to describe the principles underlying the successful implementation of a lecture recording service in higher education. Design/methodology/approach: The paper qualitatively reviews the practices and experiences of several years of automated lecture recording at a medium-sized university in Germany. Findings: The paper concludes that there are several principles that should be followed to successfully implement lecture recordings in higher education. Practical implications: The principles described in this paper can serve as recommendations for other universities that would like to establish or optimize their own lecture recording service. Originality/value: The value of the paper lies mainly in the great amount of experience in successfully running a lecture recording service on which the principles and recommendations are based.